Composição química e teste de tetrazólio em sementes de Syagrus romanzoffiana (Cham.) Glassman - Iossi, Emerson [UNESP]; Moro, Fabiola Vitti [UNESP]; Vieira, Bruno Guilherme Torres Licursi [UNESP]; Barbosa, Rafael Marani; Vieira, Roberval Daiton [UNESP] (FapUNIFESP (SciELO), 2016)
Queen palm is a tropical species of ecological importance and economic potential in various uses, including food. However, the knowledge about the nutritional value of fruits and the estimation of seed viability are still scarce. The aims of this work were to study the biometrics and chemical composition of fruits and seeds; describe the anatomy of embryos and assess the viability of the tetrazolium test. Mature fruits were collected, processed and submitted to biometry, water content, pulp and seeds chemical composition, germination and emergence in the laboratory evaluations. For the tetrazolium test, whole embryos were immersed in solution at 40 °C for one, two, four and six hours and compared with germination. The fruit pulp is rich in carbohydrates. The tetrazolium test performed at 40 ° C and 0.2% solution for two hours is adequate to estimate seed viability.
Chemical composition and tetrazolium test of Syagrus romanzoffiana (Cham.) Glassman seeds
Keywords: Embryo; Germination; Palm; Pyrene; Queen palm